Bortezomib Use for a Critically Ill Patient with Angioimmunoblastic T-Cell Lymphoma - Motoharu Shibusawa (Case Reports in Hematology)
Angioimmunoblastic T-cell lymphoma (AITL) accounts for 18.5% of all peripheral T-cell lymphomas. There is still no gold standard chemotherapy for treating newly diagnosed AITL. This case describes the use of bortezomib in newly diagnosed AITL. A 53-year-old man with no previous illness presented with erythema and swelling in the left neck. A diagnosis of AITL was made based on the results of lymph node biopsies. AITL progression led the patient to a severely deteriorated general condition. Bortezomib was thus administered, which resulted in a reduction in lymphadenopathies, the disappearance of tumor fever, and a decrease in serum lactate dehydrogenase levels. Subsequently, the patient’s general condition gradually improved. Despite the patient’s poor condition, bortezomib was well tolerated. After bortezomib administration, the patient did not require chemotherapy for approximately 10 months. The present case indicates that bortezomib is a possible treatment option for patients with AITL.